DIFFERENCES IN VISUAL ACUITY, NUTRITIONAL STATUS AND MOTOR FUNCTION IN NEW ELEMENTARY STUDENTS IN RURAL AND URBAN AREA - Dyah Umiyarni Purnamasari; Kusnandar Kusnandar; Panuwun Joko Nurcahyo (Universitas Airlangga, 2020)
School children in rural and urban areas need attention in terms of education and health. This study was aimed to analyze diff erences in visual acuity, nutritional status and motor function among school-age children in rural and urban areas. This was an analytic observational with cross-sectional design. As much as 57 students at SD Sokanegara and Kedungbanteng elementary school was recruited by purposive sampling method with inclusion criterias including fi rst grade of elementary school student in healthy condition. Visual acuity data was examined by using Snellen Chart, nutritional status data by anthropometric measurements of body weight and height was calculated using the BMI for age index, while motor function was obtained by Carpenter Motor Ability Test measurements. Data was analyze using the Mann Whitney test. The results showed there were diff erences in visual acuity (p= 0.001) and nutritional status (p= 0.027) in rural and urban school children, while motor function did not show any signifi cant diff erence (p= 0.783). It is recommended to increase outdoor activities as a protection against visual acuity